2001
DOI: 10.1139/h01-017
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Force Loss With Prolonged Stretching

Abstract: The purpose of this study was to investigate factors underlying the force loss occurring after prolonged, static, passive stretching. Subjects were tested before and 5-10 min following 20 min of static, passive stretching of the quadriceps (N = 12) or a similar period of no stretch (control, N = 6). Measurements included isometric maximal voluntary contraction (MVC) force, surface integrated electromyographic (iEMG) activity of the quadriceps and hamstrings, evoked contractile properties (twitch and tetanic fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
274
7
47

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 288 publications
(353 citation statements)
references
References 28 publications
25
274
7
47
Order By: Relevance
“…Several factors, which probably play a negative or positive role in sprint and CMJ, have been previously reported such as neural inhibition (Behm et al 2001), mechanical factors (Nelson and Sidaway 2002), reduced muscle temperature after SS (Mohr et al 2004) and reduced blood flow (Poole et al 1997). However, the precise mechanism that leads to stretch-induced sprint impairment is still not clear (Behm et al 2001). Regarding the CMJ, Kubo et al (2007) reported that prestretch augmentation of both CMJ and Drop Jumps (DJ) was related to tendon stiffness.…”
Section: Jpes ®mentioning
confidence: 99%
“…Several factors, which probably play a negative or positive role in sprint and CMJ, have been previously reported such as neural inhibition (Behm et al 2001), mechanical factors (Nelson and Sidaway 2002), reduced muscle temperature after SS (Mohr et al 2004) and reduced blood flow (Poole et al 1997). However, the precise mechanism that leads to stretch-induced sprint impairment is still not clear (Behm et al 2001). Regarding the CMJ, Kubo et al (2007) reported that prestretch augmentation of both CMJ and Drop Jumps (DJ) was related to tendon stiffness.…”
Section: Jpes ®mentioning
confidence: 99%
“…The literature describes another possibility. Static stretching of stretched muscle reduces EMG (Behm, Button, & Butt, 2001), motoneuronal excitability (H-reflex activity) (Behm et al, 2013), muscle spindle type I and II afferents output (Guissard, Duchateau, & Hainaut, 1988), and corticospinal pathways by group II and IV muscle afferents inputs (Amann et al, 2013). This can influence central drive of the working muscles and potentially of non-exercised muscle as well (Amann et al, 2013).…”
Section: Jpes ®mentioning
confidence: 99%
“…Diversos esportes e atividades recreativas utilizam os membros superiores no suporte ou transferência de força, e associam tais atividades à prática do alongamento como aquecimento ou mesmo como parte do processo de treinamento, visando o aumento da amplitude de movimento (ADM) (ex: judô, jiu-jitsu, basebol, ginástica olímpica, entre outros) [1][2][3][4][5] .…”
Section: Introductionunclassified
“…Entretanto, dependendo da forma como o alongamento é empregado no treinamento, este pode afetar diferentes sistemas biológicos como o neurofisiológico, hormonal, celular e mecânico, e influenciar de forma positiva ou negativa a resposta do tecido a estímulos subsequentes como a produção de força, potência ou o padrão de ativação muscular [4][5][6][7][8][9] . Diversos estudos demonstram efeitos deletérios na produção de força após exercícios de alongamento estático 5,6,10-13 e redução da atividade muscular após os exercícios de alongamento 8,14 , os quais podem estar relacionados à ajustes em diferentes mecanismos como os de inibição neural e/ou de alteração tecidual na unidade músculo-tendínea 5,6,[15][16][17] .…”
Section: Introductionunclassified